ANALISIS PEMBERDAYAAN LEMBAGA KEUANGAN MIKRO PADA MASYARAKAT MISKIN MELALUI BAITUL MAAL WA TAMWIL - Rida Nugraha; Ibdalsyah Ibdalsyah; Hendri Tanjung (Kasaba, 2017)
Baitul maal wa tamwil is an Islamic financial micro institution as intermediary aims to empower the poor. BMT Ibaadurahman has financial services to assist the poor both spiritual and material. This research found that with a group and individual approach, there positive effect on BMT members such as increasing income, developing their small business, until long and short term investment.